(untitled) (Ictus, 2022)
The Circle fo Willis is a particular formation of vessels located at the base of the brain. At some point it was named after Thomas Willis, an eminent English scientist who in his work, Cerebri Anatome, details the anatomy of the nervous system as no one before had done, particularly with regard to its vasculature. However, the historical path of descriptions of the circle of Willis until before Willis, is quite long. Many anatomists, doctors and other scientists had already made an approximation to this network of arteries, years or even centuries before Willis. So, behind the polygon name of Willis, there are many other names that deserve to be recognized.